Pembinaan Karakter Melalui Implementasi Budaya Sekolah di Sekolah Dasar - Prasetyo, Danang; Marzuki, Marzuki (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2019)
This paper is derived from the results of research aimed at uncovering character building programs through the implementation of school culture at the elementary school level. The type of research that has been carried out is a qualitative descriptive study conducted at Al Azhar 31 Islamic Elementary School in Yogyakarta. Data collection techniques used in this study were interviews, documentation, and observations which were then analyzed qualitatively, to test the validity of the data by means of triangulation of techniques and sources. The results showed that the character-building program that had been carried out through the implementation of school culture was deemed effective in shaping the character of students in primary schools. The school culture that is applied is implemented programmatically and spontaneously. The school culture has been carried out through activities: (1) Al Azhar pledges, tadarus Alquran, prayers in congregation to form religious character, (2) one day one Arabic word, mobile library in order to form a character like to read, (3) green school movements form character care about the environment, (4) the Javanese culture festival shape the character of the love of the motherland and the spirit of nationality, (5) 5S culture (spirit, smile, greetings, regards, polite) shape the character of tolerance and friendliness, (6) rules of class, reward and punishment to shape the character of discipline, hard work, and responsibility.